Pengolahan Palm Oil Mill Effluent (POME) Menggunakan Teknologi Membran Dan Pre-Treatment Koagulasi-Flokulasi - Jaksa Or Justman; Jhon Armedi Pinem; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study evaluate the performance of nanofiltration (NF) membrane system and pre-treatment coagulation and floculation in the treatment of palm oil mill effluent (POME) by varying the effect of concentration of coagulant, slow mixing speed, and transmembrane pressure. The process of coagulation-flocculation used aluminium sulfate with variation of concentration 3.5 g/l; 4.0 g/l; 4.5 g/l. The process completed with rapid stirring 200 rpm for 5 minutes and variation of slow stirring 65 rpm; 85 rpm; 105 rpm for 15 minutes, settling time for 30 minutes. Nanofiltration membrane processes conducted during the 60-minute operation on transmembrane pressure variation 6.5 bar; 7.5 bar; and 8.5 bar. In each treatment process, wastewater quality tests were carried out with biochemical oxygen demand (BOD) test parameters, chemical oxygen demand (COD), and total suspended solid (TSS). In addition, an analysis of permeate fluxes and the percentage of NF membrane rejection was also carried out. The research results obtained the best concentration of aluminium sulfate at 4.5 g/L and slow mixing speed 65 rpm i.e. of 71.04%; 75.49%; and 90.43% respectively for BOD, COD, and TSS. The research results obtained the value of most NF membrane high selectivity at transmembrane pressure 8.5 bar i.e. of 84.66%; 86.76%; and 94.95% respectively for BOD, COD, and TSS with a flux value of 6.32 L/m2.hours.Keywords: Aluminium Sulfate, Coagulation, Flocculation, Nanofiltration, Palm Oil Mill Effluent